Impact of Carbon Nanotube (CNT) Based Transport Layer for Electrons on Metal-Doped Lead-Free Double Perovskite Solar Cell - Mondal S.; De S.; Chakrabarti P.; Maity S. (My University, 2025)
This research explores numerical modeling and simulation studies of a lead-free perovskite solar cell employing (Cs2AgBi0.75Sb0.25Br6) as the absorber layer and utilizing single-walled carbon nanotubes (SWCNTs) in conjunction with metal oxides as the electron transport layer (ETL). Systematic investigation with six different carrier transport layers (both ETL and hole transport layer) along with comprehensive exploration of device physics, coupled with diverse optimization strategies concerning thickness, bandgap, and defect density (both interfacial and bulk), has been carried out. Our study reveals that the proposed configuration can achieve a remarkable device performance, approaching 29.06% efficiency with a current density of 35 mA/cm2. This achievement stands in close proximity to the Shockley–Queisser limit. It has been observed that SWCNT, with a 1.4 eV bandgap, enables favorable band alignment, extracting charge carriers efficiently and yielding an impressive 1.102 V open-circuit voltage. This work is poised to catalyze further experimental research, providing valuable insights for advancing perovskite solar cell technology. © 2011-2012 IEEE.